The Inhibitory Effect of Quercqus Persica L Extract on Herpes Simplex Virus-1 Replication on Baby Hamster Kidney Cells - A Karimi; MT Moradi; M Saedi; L Salimzadeh; M Rafieian (Armaghane Danesh Bimonthly Journal, 2011)
& Objectives: In the recent years, following the increase of drug resistant strain of viruses, there has been an increasing interest in the use of natural substances with antiviral activity with fewer side effects. One of these herbal medicines, Quercqus persica L, has shown some therapeutic effects, such as anti-bacterial and anti-viral activities. Therefore, this study was aimed to determine the minimum inhibitory concentration of hydroalcoholic extract of this plant on Herpes simplex virus-1 (HSV-1).